Influencia de las alternativas de secado, temperatura y humedad relativa sobre la calidad física y organoléptica del grano de cacao - Proaño Loor, Carmen Alejandrina (2021)
The quality of the bean and the organoleptic quality of the cocoa liquor is a concern of the producers and exporters of this product. This situation led to a trial to establish the effect of the drying alternatives on the physical and organoleptic quality of the cocoa bean and to relate the physical and sensory characteristics of the cocoa according to the maximum, minimum temperature and climatic conditions. RH. In the experiment, “slime” cocoa from national cacao plantations in Bolívar Canton and Convento Parroquia was used, processed in the collection centers of the Fortaleza del Valle corporation and the Kaacao company, analyzing by means of Fisher's analysis of variance, as a complete randomized design of 8 treatments and two repetitions, and the regular analysis, of the Taguchi methods, as an L8 (2) 7 design, where 7 factors are evaluated at two levels each. In this way, it was determined that the thickness of the drying layer influenced the weight of 100 almonds, observing that in a thickness of 6 cm it favors a greater weight (p A2. In the characteristic cocoa flavor, treatment T1 (A1B1C1D1E1F1G1) stood out, in "Strengths of the valley", with the practices: without draining, without manual disaggregation, without washing, cement line, thickness of 3 cm and with 2 times daily removal.